Triple-Band Microstripline-Fed Printed Wide-Slot Antenna for WiMAX/WLAN Operations - Ucar, Mustafa H. B.; Erdemli, Yunus E. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel triple-band microstrip antenna design is introduced for WiMAX/WLAN applications. The proposed antenna has a moderate size of 38×39×0.79 mm3 , yet offers quite well gain performance (5.6-8 dBi) over the operational bands. The antenna consists of a microstrip feedline coupled to a pair of concentric rectangular loops, as well as a split-ring element inserted within a slotted ground plane, which may also be considered as a wide-slot antenna element. In the paper, the numerical antenna design along with the corresponding measurement results is presented. An equivalent circuit modeling of the proposed design along with empirical formulae relating antenna parameters with notch frequencies is also introduced to serve as a useful design guideline.